ANALISIS MISKONSEPSI SISWA MENGGUNAKAN THREE TIER TEST MELALUI PENERAPAN MODEL PEMBELAJARAN SINEKTIK - Imelda Free Unita Manurung (Universitas Negeri Medan, 2017)
Abstract: Student Misconception Analysis Using Three Tier Test Through Application of Sinectic Learning Model. The purpose of this research to analyze student misconception using three tier test through the application of synoptic learning model. This research uses one shot case study method pre experimental. The population used in this study is the students of class VIII SMP, while the sample of research taken at random, that is as many as 34 students. The research instrument used is a three-tier test consisting of 10 questions, questionnaires, and instructional learning sheets. Based on the results of data analysis, the results obtained that through the application of the synectic learning model can minimize the students misconception on Pressure material. Each stage of synoptic learning can be done well and students are very enthusiastic about the synoptic learning model. Keywords : sinectic, three tier test, misconception Abstrak: Analisis Miskonsepsi Siswa Menggunakan Three Tier Test Melalui Penerapan Model Pembelajaran Sinektik. Penelitian ini bertujuan untuk menganalisis miskonsepsi siswa menggunakan three tier test melalui penerapan model pembelajaran sinektik. Penelitian ini menggunakan metode one shot case study pre experimental. Populasi yang digunakan dalam penelitian ini adalah siswa kelas VIII SMP, sedangkan sampel penelitian diambil secara acak, yaitu sebanyak 34 siswa. Instrumen penelitian yang digunakan adalah soal three tier test yang terdiri dari 10 soal, angket, dan lembar keterlaksanaan pembelajaran. Berdasarkan hasil analisis data, diperoleh hasil bahwa melalui penerapan model pembelajaran sinektik dapat meminimalisir miskonsepsi siswa pada materi Tekanan. Setiap tahapan pembelajaran sinektik dapat terlaksana dengan baik dan siswa sangat antusias terhadap model pembelajaran sinektik. Kata Kunci : sinektik, three tier test, miskonsepsi